Technical and Economic efficiency of the ruminants feed on Date Seed in Matrouh Governorate - Mansour, Sherine .F.; El-Bassiony, Moharram .F.; El-Hawy, Ahmed. S. (International Journal of Environment, Agriculture and Biotechnology, 2019)
Ruminants occupies an advanced rank between farm livestock, due to its suitability to life under difficult environmental conditions, especially in Egyptian desert governorates. The high cost of sheep and goat nutrition lead to low the animal meat unit productivity, and low the producer's profit, which facing many investors in the field of sheep and goat breeding in the Egyptian desert governorates.The problem of the study is the high cost of ruminants nutrition (around 60% from the variable total costs), despite there are many high nutrition values of agriculture residues which can enter in the composition of nutrition diet for sheep and goat. The research aims identify the optimal diet for fatting ruminants in order to maximize the productivity of sheep on one side and on other hand to minimize the cost of sheep nutrition.The research was based on the results of the experiment, that was carried out during the period from April 2017 to March 2018 at Matrouh Resource Development Center, that belongs to the Desert Research Center. The main result is that date seeds as a cheap source of energy, might be used successfully and economically in small ruminant rations during different physiological stages without adverse effects, due to estrogen-like compounds, on their productive and reproductive performance.